Hubungan Status Gizi Dan Tingkat Kebugaran Jasmani Terhadap Prestasi Hasil Belajar Mahasiswa - Kusmiyati Kusmiyati; Rama Cipta Prasetia; Fiko Adiansah (Lembaga Pengembangan Kinerja Dosen, 2022)
This study is aimed at finding out the relation between nutrition status and physical fitness level with the learning achievement of sport students living in the sport dormitory. The study is correlation research involving nutrition status and physical fitness level as independent variables and learning achievement as the dependent variable. Study population refers to all students living in the dormitory. Using purposive sampling, 23 students of the IKORA study program are chosen as the research subjects. Results of the study show the following. There is no significant correlation (p.>0,05) between nutrition status and achievement. There is significant correlation (p.>0,05) between physical fitness level and achievement. There is significant correlation (p.>0,05) between nutrition status and physical fitness level with achievement. Physical fitness level gives the bigger effective contribution of 28,68%. Nutrition status gives effective contribution of 10,32%.